Education System of The Republic of Uzbekistan: Educational Program and Assigned Qualifications - Berdiyeva Nafisa Abdumalik kizi (Proceedings of The ICECRS, 2019)
This article describes the modern structure of the education system of the Republic of Uzbekistan,reformed in the last decade in accordance with the national program adopted in the Republic fortraining of personnel implemented in Uzbekistan educational programs at various levels, assigned totheir completion of qualifications and educational documents confirming these qualifications.